Microstructure and impression creep characteristics of squeeze-cast AZ91 magnesium alloy containing Ca and/or Bi - Majhi J.; Mondal A.K. (My University, 2025)
The effects of Ca and/or Bi additions on the microstructural modification and creep characteristics of the squeeze-cast AZ91 alloy have been addressed. Both the single as well as the mixed contents of Ca and Bi in the AZ91 alloy refine the grain size of primary α-Mg and reduces the β-Mg17Al12 phase considerably. The effect is more noticeable in combined additions than in the individual additions. The reticular-shaped Al2Ca and needle-shaped Mg3Bi2 phases additionally form with the α-Mg and β-Mg17Al12 phases because of the sole Ca and Bi addition in the AZ91 alloy. The Al2Ca and Bi3Ca5 phases are formed when Ca and Bi are added together, suppressing the Mg3Bi2 phase formation. The modified AZ91-based alloys containing Ca and/or Bi exhibit improved creep behaviour than the AZ91 alloy at all the stress and temperature levels tested. The individual additions of the elements in the AZ91 alloy shows higher creep rate than the combined additions. The individual Ca addition is better than the Bi addition for resisting the creep deformation in the AZ91 alloy as the Al2Ca phase in the AZX911 alloy has superior thermal stability compared to that of the Mg3Bi2 phase in the AZB910 alloy. The AZXB9120 (AZ91 with 2.0Ca and 0.5Bi (wt%)) exhibits the best creep performance owing to the lower volume fraction of β-Mg17Al12 phase and existence of larger quantity of thermally stable Al2Ca and Bi3Ca5 phases. The values of stress exponents and activation energies concludes that the dominant creep mechanism for all the alloys is dislocation climb aided by pipe diffusion. Microstructural investigation following creep indicates that the β-Mg17Al12 phase was broken into small pieces. In contrast, the thermally stable Al2Ca, Mg3Bi2 and Bi3Ca5 phases preserved their continuity, which resulted in piled-up dislocations and tangling of dislocations in the interior of the α-Mg grains that leads to the improved resistance to creep deformation of the modified AZ91 alloys. © 2018 Elsevier B.V.